Analysis of Coat Color Changes and Hormone Levels in Korean Brindle Cattle - Hae-Lee Lee; Jae-Hee Park; Yong-Su Kim; Jong Gug Kim (The Korean Society of Animal Reproduction and Biotechnology, 2015)
The aim of this study was to determine the relationship between the coat color appearance of Korean brindle cattle and the changes of relevant hormone levels that may affect the hair pigmentation during different stages of growth and maturation. In mature cattle, levels of both ACTH and DHEA in Korean brindle cattle with brown color were significantly higher than those with black color (p<0.05). Levels of α-MSH in Korean brindle cattle with whole brindle (?50%) color were significantly higher than those with brown color (p<0.05). In calves of Korean brindle cattle at 2 to 6 months, the concentration of estradiol was significantly higher in calves with whole brindle color than those with part brindle color (p<0.05), when the coat color was confirmed. After 6 month of coat color confirmation, levels of testosterone and ACTH increased in calves with part brindle color and were significantly higher than those with whole brindle color (p<0.05). In calves of Korean brindle cattle at 1 or 2 months, there were no significant differences in hormone levels of estradiol, ACTH, DHEA and α-MSH between the calves with brindle color and brown color, except estradiol before brindle color appearance. Changes of relevant hormone levels at different stage of growth and maturation may affect the pigmentation of coat during the development of cattle. In addition to the current study correlating the different coat colors with relevant hormone levels, investigation of the coat color associated genes expressed in Korean brindle cattle may further clarify the mechanisms of coat color changes during their development.